THE CORRELATION BETWEEN SERVICE QUALITY AND THE LEVEL OF SATISFACTION OF BPJS PATIENTS IN THE INPATIENT ROOM HOSPITAL KH. ABDURRAHMAN SYAMSURI PACIRAN - Muhammad Sudrajad; Dwi Kurnia Purnama Sari; Surotul Ilmiah; Didik Suharsoyo (International Nutrition and Health Administrations Journal, 2023)
Patient satisfaction depends on the quality of service provided. A service is said to be good by patients if the services provided can meet the needs or expectations of patients. This study was to determine the relationship between service quality and the level of satisfaction of BPJS patients in the Inpatient Room of KH Abdurrahman Syamsuri Paciran Hospital. The research used was quantitative research with a cross-sectional study approach. The population was all patients of BPJS participants who underwent treatment in the Inpatient Room of KH Abdurrahman Syamsuri Paciran Hospital—numbered 15 people. Sample withdrawal using accidental sampling with a sample size of 14 respondents. The data analysis performed was univariate and bivariate with the Spearmen rho test. The results showed that there was a relationship between reliability (p=0.001), empathy (p=0.001), responsiveness (p=0.001), and amenity (p=0.001). There was no relationship between assurance (p = 0 . 491), number of personnel (p=0.106), and availability of drugs (p=0.143) with BPJS patient satisfaction in the Inpatient Room of KH. Abdurrahman Syamsuri Paciran Hospital. The study concludes that there is a relationship between service quality and the level of satisfaction of BPJS patients in the Inpatient Room of KH. Abdurrahman Syamsuri Paciran Hospital. The results of this study are input to management to improve service quality based on the level of patient satisfaction of BPJS users. So that it will improve the quality and patient satisfaction.